A support framework for the migration of e-Government services to the cloud. - Cardoso, Abílio (2015)
Public and federal agencies from countries around the world are increasingly providing information technology based services via the Internet - known as e-government. Several of the general requirements of e-government services are satisfactorily met by the emerging Cloud Computing paradigm that promises a number of benefits such as service elasticity (the ability to handle peaks and troughs of demands); optimization of costs; capacity to handle large volumes of data; and a generalized model of Internet-based access for end-users. For this reason, it is no surprise that Cloud related technologies are gradually leveraging e-government platforms. In this chapter, a support framework is outlined that complies with and extends the well-known ITIL (Information Technology Infrastructure Library) set of best practices for IT (Information Technology) service management. It is suggested that the proposed framework can be usefully deployed to assist in the process of migrating e-government services provision to the Cloud Computing environment.